Coherent-resonance enhancement of sensing at the exceptional points - Chen, Jingming (2024)
The branch point singularities in the Riemann surface of the parameter space are known as the exceptional points (EPs), at which two or more eigenvalues and their associated eigenvectors simultaneously coalesce. The abrupt bifurcation property around an EP shows a strong spectral response to external perturbations, and hence, is exploited as a new approach to ultrasensitive sensors. Recently, an intriguing proposal for implementing second-order EPs in optical resonators with external perturbations has shown the superiority of non-Hermitian degeneracies in the enhancement of sensing. Of particular importance is further improving the sensitivity to even greater extents. To this end, a novel physical mechanism is proposed, namely introducing extra resonances of external Rayleigh scatterers to accomplish strong-coupling augmentation in sensing. The results, grounded by both theoretical coupled-mode-theory calculations and experimental spectral-domain measurements, show that the EP-based sensor working at the coherent resonance equips simultaneously substantial perturbation strength and azimuth sensitivity even subjected to extremely weak perturbations. This work paves the way to a new class of highly functional tunable sensors for applications in optics, microwave and acoustics.